Khonsari's cardiac surgery : safeguards and pitfalls in operative technique - Ardehali, Abbas; Chen, Jonathan M. (Wolters Kluwer, 2017)
"Unique in the field of cardiac surgery, Khonsari's Cardiac Surgery: Safeguards and Pitfalls in Operative Technique details the most important techniques in a concise, readable, and richly illustrated format, with a focus on avoiding and managing surgical pitfalls and complications. From general considerations through the surgical correction of acquired and congenital heart conditions, it provides a wealth of practical, hands-on guidance to help both seasoned and less-experienced cardiac surgeons achieve optimal outcomes"--Publisher's description